Chroma key background detection for digital video using statistical correlation of blurring artifact - Bagiwa, M.A.; Wahab, A.W.A.; Idris, M.Y.I.; Khan, S.; Choo, K.K.R. (Elsevier, 2016)
Video editing software can be used to combine different videos into one video using the chroma key feature. However, detecting such video manipulation is an understudied topic. Digital forgers may present a manipulated video from chroma key composition as evidence in court, thus creating a severe problem. In this paper, we propose a blind detection technique designed to analyze the statistical correlation of blurring artifact extracted from a digital video. This technique allows us to detect chroma key forgery in a manipulated composite video. Findings from our experiments demonstrate that the proposed detection technique can adequately determine the presence of manipulation on a video using chroma key, with a true positive detection rate of 91.12% and a false positive detection rate of 1.95%.